Between Fascism and Conservative Authoritarianism. The Estado Novo Regime In Portuguese History Textbooks (1975-2023) - Neto, Sérgio Gonçalo; Serrano, Clara (Revista de Historia Social y de las Mentalidades, 2024)
In Portugal, the dictatorial Estado Novo regime (1933-1974) ended with the Carnation Revolution of 25 April, which put an end to thirteen years of colonial war on several fronts. Since then, the regime has been the subject of an intense historiographical debate that has ultimately covered its multiple dimensions and realities. Part of this debate has focused on its possible “fascist” nature. The aim of this text is to use a comparative methodology (qualitative and quantitative) to analyse post-25 April history textbooks to see how the approach to the dictatorship might have evolved.
Keywords: Estado Novo; Fascism; Textbooks; History Teaching